The Current State of Research on the History of Christianity in China in Korean Academic Circles - LI, Huiyuan (Journal of Research for Christianity in China (JRCC), 2023)
Preface Studies on Nestorianism and the Yelü-Kewen Religion Studies on the History of Catholicism Studies on the History of Protestantism History of Sino-Korean Relations